Práticas de governança corporativa adotadas pelas operadoras de planos de assistência à saúde classificadas como cooperativas - Lobo, Gleidson Sobreira (2010)
In recent years, good corporate governance practices have become a competitive advantage for organizations contributing to a more transparent and professional management, minimizing agency conflicts and maximize the organization's results to add value to the owners and may also influence the consumer’s decision to purchase products and services. Therefore, this study aims to investigate the corporate governance practices that are adopted by a health plan operators classified by the Agência Nacional de Saúde Suplementar - ANS as a medical cooperative in light of the recommended practices for companies in general. We used a descriptive research, with qualitative and quantitative approach, using as a research strategy the survey, with support of literature and documents. We chose to study the health plan operators in system Unimed considered by the ANS as large in order, seeking to identify their chief executives and documents that the information system necessary to accomplish the goals it is proposed that work. The study revealed that operators classified in the cooperative medical modality have an organizational structure consistent with the adoption of best corporate governance practices recommended by the literature on business in general, following further compliance with the Act 5.764/1971 establishing and the measures emanating by regulators of their activities. With the research, concludes that health plan operators investigated following good corporate governance practices recommended by Instituto Brasileiro de Governança Corporativa (2009) and recommendations on the governance of the Banco Central do Brasil (2008), according to the results obtained through the analysis and the model used to define the degree and level of adoption of such practices. The results also showed that the amount of beneficiaries, employees and associates (cooperative) have no influence on the adoption of governance practices at the carriers studied.